Role of academic libraries in promoting information literacy among students of higher learning institutions - Hassan, Basri; Mansor, Yushiana (IIUM Press, 2009)
Introduction : In this age of globalisation, so much emphasis has been given on equipping students with the right skills and competencies in order for them to gain competitive edge. For students to be active global players in the knowledge-based economy, where information is a commodity and where information is power, higher learning institutions are entrusted in producing a new breed of graduates. Students have to be actively engaged in the process of infonnation seeking for research, assignments, and decision-making. Effective decision making, however, can only be achieved by having the right information, in the right place, in the right format, at the right time.